2015
DOI: 10.1517/14712598.2015.1103733
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of CT-P13 (Infliximab biosimilar) used as a switch from Remicade (infliximab) in patients with established rheumatic disease. Report of clinical experience based on prospective observational data

Abstract: The clinical effectiveness of INB in both PROs and disease-activity measures was comparable to INX during the first year of switching, with no immediate safety signals. Subjective reasons (negative expectations) may play a role among discontinuations of biosimilars. Larger patient numbers and longer follow-up are necessary for confirming this clinical experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 11 publications
5
72
2
2
Order By: Relevance
“…9,10 About 50% of patients with psoriasis who start infliximab have to discontinue treatment within the first year because of loss of efficacy attributed to antiinfliximab antibodies and a faster drug clearance.…”
Section: Cohort 1: Patients With Psoriasis Who Switched From the Inflmentioning
confidence: 99%
“…9,10 About 50% of patients with psoriasis who start infliximab have to discontinue treatment within the first year because of loss of efficacy attributed to antiinfliximab antibodies and a faster drug clearance.…”
Section: Cohort 1: Patients With Psoriasis Who Switched From the Inflmentioning
confidence: 99%
“…Clinical evidence is evolving in favor of switching patients from infliximab-biologic to its biosimilar [15][16][17][18]. In this context, patients currently on infliximab-biologic could all be considered for biosimilar-infliximab.…”
Section: Discussionmentioning
confidence: 99%
“…At least one phase III, randomized clinical trial is then performed in a sensitive patient population representative of those included in an approved indication for the reference biologic, to demonstrate equivalent efficacy and comparable safety and immunogenicity of the biosimilar and its reference biologic. Post-marketing authorization studies, together with real-world data from registries and clinical centers, provide additional confirmation for the long-term effectiveness, safety, and immunogenicity of approved biosimilars [2,[15][16][17][18][19][20][21]. All this taken together comprises the totality of evidence for a biosimilar, highlighting the rigorous process in which biosimilars are developed and monitored [2].…”
Section: Perception Of Biosimilars: Awareness and Communication Gapsmentioning
confidence: 99%
“…Recently, this nocebo effect has also been considered in patients switching from reference biologics to biosimilars [15,18,36]. In observational studies, 16-28% of patients were found to discontinue CT-P13 biosimilar following C 3 months of treatment [15,18,36].…”
Section: Nocebo Effect In Patients Prescribed Biosimilar Agentsmentioning
confidence: 99%
See 1 more Smart Citation